2012
DOI: 10.1007/s12035-012-8327-0
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein and Neuronal Cell Death

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder affecting ∼1 % of people over the age of 65. Neuropathological hallmarks of PD are prominent loss of dopaminergic (DA) neurons in the substantia nigra and formation of intraneuronal protein inclusions termed Lewy bodies, composed mainly of α-synuclein (αSyn). Missense mutations in αSyn gene giving rise to production of degradation-resistant mutant proteins or multiplication of wild-type αSyn gene allele can cause rare inherited forms of PD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 209 publications
(282 reference statements)
4
72
0
3
Order By: Relevance
“…S6). Hence, these findings suggest that AMPK might mediate DAergic cell death upon MPP + treatment primarily through excessive autophagy, in keeping with the controversial view of apoptosis in PD (38). Accordingly, in PIKE-null and Fyn-KO mice, overexpression of AMPK-DN suppressed MPTP-induced autophagy in the substantia nigra, leading to improved DAergic neuronal survival and motor function (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…S6). Hence, these findings suggest that AMPK might mediate DAergic cell death upon MPP + treatment primarily through excessive autophagy, in keeping with the controversial view of apoptosis in PD (38). Accordingly, in PIKE-null and Fyn-KO mice, overexpression of AMPK-DN suppressed MPTP-induced autophagy in the substantia nigra, leading to improved DAergic neuronal survival and motor function (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Neuropathological hallmarks of PD are a prominent loss of dopaminergic neurons in the substantia nigra pars compacta and formation of the protein inclusions called Lewy bodies (LB) and Lewy neurites (LN) in neuronal somas and processes, respectively [1]. The major component in these inclusions is α-synuclein (αSyn), which is a 140 amino acid protein of unknown function, usually abundant in presynaptic terminals of nerve cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Genome-wide studies have identified SNCA and MAPT, genes encoding α-synuclein (α-Syn) and Tau, respectively, as having strong association to the genesis of PD. [2][3][4] Although the precise etiology of PD remains a mystery, SNCA amplifications and mutations directly link α-Syn dysfunction to disease causation, 5,6 firmly establishing a role for α-Syn in sporadic and familial PD, respectively. α-Syn can be phosphorylated at several sites, 7 and the predominance of α-Syn phosphorylated at serine 129 (S129) in Lewy bodies 8 suggests its phosphorylation status at S129 has an important pathological role.…”
mentioning
confidence: 99%